Fracture-dislocation of femoral head associated with acetabular fracture: case report - Reyes Cabrera, Johanna María; Caballero Trenado, Jose Ventura; Ganso Pérez, Abel (Revista Colombiana de Ortopedia y Traumatología, 2016)
The femoral head fracture dislocation is a rare injury. We present a case of a fracture dislocation Pipkin IV, the treatment accomplished and the clinical radiological follow-up. In worldwide literature there are few reported cases with this injury. We have performed a bibliographic review of this topic. Evidence level: IV.